(NIE)RELIGIJNA MORALNOŚĆ KATOLIKÓW W POLSCE - Boguszewski, Rafał (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In this article, based on the results of quantitative research conducted by CBOS in the years 2005–2013, the author identifies the impact of religiousness on the moral directives recognized by Catholics in Poland and on their approach to various kinds of moral attitudes and behaviours. It turns out that the significance of religion, which is still an important aspect of life in Poland, is gradually decreasing. CBOS data collected over the last couple of years confirms the hypothesis of a progressive gap between morality and religiousness and shows a significant increase in moral relativism in the attitudes of Catholics. But the increasing autonomy of religion and morality does not mean, as it seems, the complete disintegration of moral values and norms, but rather their reorganization and subjectivisation in the process of creating oneʼs own code of conduct.